Evaluation of the Antimicrobial Efficacy of Red Ginger Extract (Zingiber Officinale Rosc. Var Rubrum) Against Staphylococcus aureus Using the Kirby-Bauer Disc Diffusion Method - Sitti Qonitah; Nasrudin Andi Mappaware; Muh. Wirawan Harahap; Ida Royani; Nurfachanti Fattah (Poltekkes Kemenkes Surabaya, 2025)
The increasing prevalence of antibiotic-resistant bacteria, particularly Staphylococcus aureus, necessitates the exploration of alternative treatments. This study investigates the antibacterial efficacy of red ginger extract (Zingiber officinale Rosc. var. Rubrum) against Staphylococcus aureus using the Kirby-Bauer disc diffusion method. Fresh red ginger was extracted using 96% ethanol, and varying concentrations (50%, 75%, and 100%) were tested for their ability to inhibit bacterial growth. The results indicated that at 50% and 75% concentrations, the inhibition zones ranged from 6.2 mm to 9.5 mm, categorizing them as resistant. In contrast, the 100% concentration yielded inhibition zones between 14.2 mm and 16.9 mm, classified as intermediate. These findings suggest that red ginger extract possesses significant antibacterial properties, particularly at higher concentrations, although it remains less effective than standard antibiotics like chloramphenicol. The study highlights the potential of red ginger extract as a natural alternative for treating Staphylococcus aureus infections, emphasizing the need for further research on dosage variations, solvent types, and toxicity assessments to optimize its therapeutic application. Overall, red ginger extract could serve as a promising candidate in the fight against antibiotic-resistant bacterial infections.